Modularisierung von und in beruflichen Bildungsgängen : Zwischen Anspruch und Wirklichkeit - Pilz, Matthias [Verfasser]; Li, Junmin [Verfasser] (My University, 2016)
"The modularisation of educational programmes in general education, in vocational education and training (VET), and in the academic sector has been an important topic in many European countries. In Germany, the debate on modularisation has been taking place in the fields of VET for years. The pros and cons of modularisation have been discussed intensively. However, these argumentations are mostly based on surmises. Empirical data are almost entirely lacking. Our stuedy addresses this lack of research. Based on two modular training programmes, we explore the differences between policy claims on modularisation and what actually happens in practice." (authors' abtract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 1.1.3 Modulorientierung; S 2.3.2 Programme in der Berufsbildung; Berufsausbildung; Modularisierung; Beruflichkeit; Ausbildungsbaustein; Ausbildungsberuf; Wahlqualifikation